Neuropsychological profile and clinical effects of arginine treatment in children with creatine transport deficiency - Chilosi Annamaria; Casarano Manuela; Comparini Alessandro; Battaglia Francesca; Mancardi Margherita; Schiaffino Cristina; Tosetti Michela; Leuzzi Vincenzo; Battini Roberta; Cioni Giovanni (Orphanet Journal of Rare Diseases, 2012)
Abstract Background SLC6A8, an X-linked gene, encodes the creatine transporter (CRTR) and its mutations lead to cerebral creatine (Cr) deficiency which results in mental retardation, speech and language delay, autistic-like behaviour and epilepsy (CRTR-D, OMIM 300352). CRTR-D represents the most frequent Cr metabolism disorder but, differently from Cr synthesis defects, that are partially reversible by oral Cr supplementation, does not respond to Cr treatment even if precociously administrated. The precursors of Cr are the non-essential amino acids Glycine (Gly) and Arginine (Arg), which have their own transporters at the brain–blood barrier level and, therefore, their supplementation appears an attractive and feasible therapeutic option aimed at stimulating Cr endogenous synthesis and, in this way, at overcoming the block of Cr transport within the brain. However, until now the effects of Arg and/or Gly supplementation on Cr brain levels and behaviour have been controversial. Methods In this study five Italian male patients affected by CRTR-D were supplemented with oral L-Arg at a dosage of 300 mg/kg/day divided into 3 doses, for 24–36 months. Biochemical and plasmatic amino acids examinations and thyroid hormone dosages were periodically performed. Moreover, Proton and Phosphorus Magnetic Resonance Spectroscopy (MRS) was monitored during follow-up in concurrence with neuropsychological evaluations. Results During L-Arg treatment a clinical improvement in motor skills and to a lesser extent in communication and attention was observed. In addition, all patients had a reduction in the number and frequency of epileptic seizures. Daily living skills appeared also to be positively influenced by L-Arg treatment. Moreover, Total Cr and especially PhosphoCr, evaluated by proton and phosphorus spectroscopy, showed a mild increase, although well below the normal range. Conclusion This study provides information to support the effectiveness of L-Arg supplement treatment in CTRT-D patients; in fact the syndromic pattern of cognitive and linguistic deficit presented by CRTR-D patients was partially altered by L-Arg supplementation especially at a qualitative clinical level. Oral L-Arg may represent not only a protective factor towards a further cognitive decline, but can lead to the acquisition of new skills.